Best Practices for Contract Management in U.S. Infrastructure Development Projects - Chikaome Chimara Imediegwu,; Okeoghene Elebe,; Opeyemi Morenike Filani,; Andikan Udofot Umana,; Muritala Omeiza Umar, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
Effective contract management is crucial for the success of U.S. infrastructure development projects, given the complexity and scale of these undertakings. This paper explores the key elements of contract management, identifies common challenges, and outlines best practices to enhance project outcomes. The analysis covers essential components such as contract negotiation, risk management, and compliance while also addressing the legal, financial, and operational risks that can arise. Furthermore, the paper highlights the role of technology and digital tools in streamlining contract management processes and emphasizes the importance of collaboration and communication among stakeholders. The conclusion offers insights into the impact of best practices on project success and discusses future trends and recommendations for improving contract management in the evolving landscape of U.S. infrastructure development.
Keywords: Contract management; Infrastructure development; Risk management; Digital tools; Best practices